The role of social media in shaping purchasing decisions in Phnom Penh, Cambodia - Simeng Ly; Hong Soun (Southeast Asian Journal of Service Management, 2026)
The rapid evolution of social media has transformed consumer behavior, making it a critical tool for influencing purchasing decisions in the digital age. This study, titled "The Role of Social Media in Shaping Purchasing Decisions in Phnom Penh, Cambodia" by addressing two key research questions: (1) What are the key factors in social media that influence consumer purchasing decisions in the digital age? (2) What are the challenges in purchasing through social media? To achieve this, a systematic methodology was employed, encompassing sample design, data collection, and statistical analysis. SPSS was used to conduct descriptive statistics, regression, and factor analysis. Additionally, reliability testing, such as Cronbach’s Alpha, was conducted to ensure the consistency of survey responses. Based on a survey of 394 participants, where 58.9% were men and 41.1% were women, with a significant proportion aged 26-30, results showed that social media usage was prevalent, with most respondents engaging daily. Findings revealed that all key factors in social media such as social media engagement, influencer credibility, peer recommendations, level of consumer awareness, digital literacy, and consumer protection mechanisms had a significant influence on purchasing decisions, as reflected in a Model Summary of Regression shown R-value 84%, R-square 70.6%, and Adjust R-square 70.1% with significance <0.001. Based on Regression Coefficient showing P-value of all independent variables are <0.01 which selecting a significance level 1% to accept. In addition, a key challenge identified in the survey is the discrepancy between advertised and actual products on social media, which undermines consumer trust. This issue highlights the need for accurate product representation, stricter ad transparency, and stronger return and refund policies to restore buyer confidence in social commerce. This research highlights the growing impact of social media in consumer behavior and provides insights into the challenges and opportunities for businesses and consumers in the digital marketplace.